2018
DOI: 10.1007/s12035-018-0874-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Histone Deacetylase Activity to Arrest Cell Growth and Promote Neural Differentiation in Ewing Sarcoma

Abstract: There is an urgent need for advances in the treatment of Ewing sarcoma (EWS), an aggressive childhood tumor with possible neuroectodermal origin. Inhibition of histone deacetylases (HDAC) can revert aberrant epigenetic states and reduce growth in different experimental cancer types. Here, we investigated whether the potent HDAC inhibitor, sodium butyrate (NaB), has the ability to reprogram EWS cells towards a more differentiated state and affect their growth and survival. Exposure of two EWS cell lines to NaB … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Inhibition of EWS-FLI1 transcript after combination treatment was similar or slightly higher than SAHA as a single agent, suggesting that SAHA plays a predominant role within this combination. Recently, Souza et al have demonstrated that sodium butyrate (a potent class I and IIa HDAC inhibitor) induced suppression of cell proliferation accompanied by reduced transcriptional expression of the EWS-FLI1 [ 41 ]. A stronger effect on the inhibition of EWS-FLI1 protein was found with combination treatment in comparison to monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of EWS-FLI1 transcript after combination treatment was similar or slightly higher than SAHA as a single agent, suggesting that SAHA plays a predominant role within this combination. Recently, Souza et al have demonstrated that sodium butyrate (a potent class I and IIa HDAC inhibitor) induced suppression of cell proliferation accompanied by reduced transcriptional expression of the EWS-FLI1 [ 41 ]. A stronger effect on the inhibition of EWS-FLI1 protein was found with combination treatment in comparison to monotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, novel HDACi have been proposed to counteract sarcoma CSCs. These compounds not only sensitized sarcoma cells to chemotherapy by reversing multidrug resistance, but also increased treatment responses when in combination with chemotherapy [125][126][127][128]. In a phase I/II clinical study evaluating the HDACi belinostat in combination with doxorubicin, in a cohort of 41 STS patients, the response rate was modest but median PFS was 6 months.…”
Section: Epigenetic Modulationmentioning
confidence: 99%
“…Furthermore, it has been observed that suppression of the fusion oncogene or direct downstream target genes can facilitate differentiation of fusion-positive sarcoma cells in combination with adequate differentiation-stimulating media in EwS [53], SS [29,54], and ARMS [55]. Hence, differentiation induction by RNAi and differentiation inducing drugs (such as LSD1 and HDAC inhibitors [56,57]) could be therapeutically implemented in pediatric sarcoma treatment regimens, as exemplified by treatment of acute promyelocytic leukemia with all-trans-retinoic acid [58].…”
Section: Targeting Mrna Transcripts Of Fusion Oncoproteins Using Rna mentioning
confidence: 99%
“…One group of epigenetic regulators are HDACs, which remove acetyl groups from lysine residues of histone chains and thereby regulate gene expression [132]. Indeed, in preclinical models of EwS, HDAC inhibitors have been shown to induce apoptosis, promote differentiation, and reduce tumor growth in xenograft experiments [57,133]. Antitumorigenic activity of HDAC inhibitors has also been reported in preclinical models of SS and ARMS [134][135][136][137][138].…”
Section: Targeting Protein-dna Interactions Of Fusion Oncoproteins Inmentioning
confidence: 99%